Improved dispersion performance and interfacial compatibility of covalent-grafted MOFs in mixed-matrix membranes for gas separation - Chongqing Wang; Guangjie Ren; Kaifeng Wei; Donghui Liu; Tingting Wu; Jinlong Jiang; Junfeng Qian; Yichang Pan (Green Chemical Engineering, 2021)
Mixed-matrix membranes (MMMs) have received much attention due to their processable advantages of polymer and high permeability and/or selectivity of porous metal-organic frameworks (MOFs) fillers. However, the interfacial defects caused by poor interaction between MOFs with polymers and the agglomeration phenomenon caused by uneven dispersion of MOFs are common problems in mixed-matrix membranes. Currently, the priming protocol is one of solutions to the above problems, but it cannot precisely regulate the dispersion of particles and the interfacial compatibility between two phases. Herein, covalent grafting of polyimide 6FDA-Durene onto the surface of UiO-66-NH2 can mitigate the aggregation of fillers inside the polymeric matrices and improve the interfacial interaction between two phases, thus significantly improving the CO2/CH4 separation performance on the as-synthesized MMMs. The explored gas transport mechanism indicated that the improved separation was due to the raise of solubility selectivity. Furthermore, the stronger covalent bond between fillers and polyimide than physical interaction of priming protocol also endows the improved anti-plasticization phenomenon for CO2/CH4 separation.